Stress and oncological nursing: studies at Center of Researches in Nursing (CEPEN) - Rafaela Andolhe; Laura da Azevedo Guido; Graciele Fernanda da Costa Linch (Universidade Federal Fluminense, Escola de Enfermagem Aurora de Afonso Costa, 2008)
This work was elaborated with the aim of identifying the theoretical tendencies of the knowledge produced in the nursing concerning stress, as well as observing in the publications that it was researched about stress among oncological nurses. It is a bibliographical study carry out in the dissertations and thesis abstracts contained in CEPEN - Center of Researches in Nursing among from 1979 to 2005. 18 abstracts were found, analyzed and organized in two categories: A) Stress among nurses and nursing team, and B) Stress and nursing oncológica. The analyzed of data demonstrated that the researches about stress and nursing are increasing, but a gap was observed concerning researches that focus stress level among nurses oncológicos.